THE INFLUENCE OF ADVERTISEMENT TO VISITING FREQUENCY IN BONO TOURISM OBJECT DESA TELUK MERANTI KABUPATEN PELALAWAN PROVINSI RIAU ( A CASE STUDY OF DJARUM SUPER ADVENTURE DUBSTEP VERSION ADVERTISEMENT) - Hastuti, Siti; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The purpose of this research is to find out how djarum super adventure dubstep version influence the improvement of visisting in Bono tourism object Desa Teluk Meranti Kabupaten Pelalawan Provinsi Riau. The hypotheses is to find out the influence of advertisement to improvement of visisting in Bono tourism object Desa Teluk Meranti Kabupaten Pelalawan Provinsi Riau.This is a quantitative research with 50 sample. In choosing the sample, writer used accidental sampling, which is purposive sampling. Data is collected by questionaires. Data analyzin technique is validation test and reability, simple linear regression and coefficient determination.Result shows that variable of music, storyboard, script, and slogan influence dependent variable (Y). Coeficcient determination (R square) 34% shows that independent variable influence dependent variable. The rest 66% are influenced by other independent variable which are not stated here.Key word: advertisement, visiting frequency, SPSS